Экспериментальные исследования режимов кузнечной протяжки заготовок с обкаткой в комбинированных бойках - Кухарь, В. В.; Василевский, О. В. (НТУ "ХПИ", 2013)
The methodic of experimental research of form-changing and force parameters during stretch forging of billets with rolling to diameter by combined anvils is worked and realized out. The depends of changing of force parameters, geometric characteristics and optimal modes of deformation of billets during stretch forging by rolling in combined anvils with different values of press upsetting and angles of rotation of billets around far axe are determinates.

Разработана и реализована методика экспериментальных исследований формоизменения и силовых параметров при протяжке заготовок с обкаткой по диаметру в комбинированных бойках. Установлены закономерности изменения силовых параметров, геометрических характеристик и оптимальные режимы деформирования заготовок при протяжке обкаткой в комбинированных бойках с различными величинами обжатий и углов кантовок заготовок вокруг продольной оси.
Keywords: поковки валов; деформация; силовые параметры; геометрические характеристики; stretch forging; combined anvils; deformation; force parameters; geometric characteristics; experimental research